Banking on Baghdad: Inside Iraq's 7,000-Year History of War, Profit, and Conflict - Black Edwin (John Wiley & Sons Inc, 2004)
In emphasizing the symbiosis of oil profits and Western imperialism in the making of modern Iraq, Black (IBM and the Holocaust) and a team of 30 researchers (whom he credits) have unearthed a wealth of historical detail, but not a satisfying framework for it. Temporal balance is also missing: the book's first 6,500 years pass in a 42-page montage of conquest and massacre, with the narrative slowing to a snail's pace during the late Ottoman and British Mandate periods to explore the interminable wranglings among Western oil companies, European governments and entrepreneur C.S. Gulbenkian over Iraqi oil concessions in the first half of the 20th century. Accounts of the Sunni-Shiite schism and the modern recrudescence of Iraqi anti-Semitism are thrown into the mix, but one gets little sense of how all these elements determine the social, economic and political turmoil of contemporary Iraq, especially since the crucial Saddam era flits by in just six disjointed pages. In the end, Black does little more with a lot of undeniably fascinating material than to invoke the "unstoppable repetition" of despotic government and violent exploitation, but his corporate-historical gleanings are more than enough to carry the book.